The journey into fatherhood: A grounded theory study - Nantaporn Sansiriphun (2018)
© 2015 Wiley Publishing Asia Pty Ltd. The objective of this study was to explore the process of transition into fatherhood for Thai men from childbirth to the postpartum period. Forty-one first-time Thai fathers were voluntarily recruited from two hospitals in Chiang Mai, Thailand, from December 2012 to June 2013. In-depth interviews were used to collect the data, which were analyzed based on grounded theory methodology. The basic social process that emerged as the core category was termed: "the journey into fatherhood." This process was divided into three phases: labor, delivery, and family beginning. Within this process, there were various situations, challenges, and pressures, which caused many changes of mood and feelings for the first-time fathers. Throughout this process, they applied various strategies to manage their concerns and needs, in order to develop into masterly fathers. Identifying the process of the journey into fatherhood provides nurses and midwives insight into the new fathers' experiences, which will enable them to be more sensitive, respectful, and effective caregivers.